Substâncias húmicas em solos de diferentes feições geomorfológicas no rebordo do planalto do Rio Grande do Sul - Menezes, Fábio Pacheco (2008)
In spite of the great importance of the soil organic matter for the sustainability of the natural systems and of agricultural production, its study remains incipient in the area of the Edge of the Rio Grande do Sul Plateau, where different research have been reporting negative aspects of the inadequate soil use. In that sense, the carbon distribution evaluation among the chemically separated fractions can supply subsidies to analyze the effects of land use on those sites. Besides that, it is important to know the role carried out by the different geomorphological features present in the area, once that the variation of the soil attributes can be different in each segment of the landscape. The purpose of this research was to evaluate the influence of the land use on the soil organic matter fractions, chemical attributes and aggregates distribution in different soil depths and landscape positions, analyzing three topossequences of soils of hillsides areas of the Edge of the Plateau. Soil characteristics such morphological, environmental, chemistries and physical, were analyzed for each soil horizon and layer. The chemical fractionation of the soil organic matter was realized to quantificate the carbon amount of the humic fractions and to determinate the amount of Fe+3 and Al3+ co-extracted with the humic substances. The results allowed to verify that the chemical and physical attributes of the soil were effected by the land use, and the position of the profile in the landscape has an important effect in the distribution of the materials in the studied topossequences. The forest showed the largest indexes of aggregation of the soil in the superficial layer and in the top of the landscape, where the larger amount of total organic carbon was verified. The amount of carbon in the fractions extracts of the soil organic matter was different for each land uses. The acid fraction carbon showed low amount in relation to the other extracts. The humina fraction corresponded to the most sensitive indicator to the change of use of the soil. Most of the soil organic matter was distributed in the alkaline-soluble fractions. However, higher values were observed at the forest due to the soil litter. Among the alkaline-soluble fractions, the humic acids were predominant, but they showed variations according to the position in the landscape. This fraction associates preferentially with Fe+3, while Al+3 showed larger affinity for the fulvic acids.